PEMILIHAN KEPALA DAERAH DAN PROSES DELIBERASI: MEWUJUDKAN KEBIJAKAN PUBLIK YANG PARTISIPATIF - Sofian, Muhamad; Muhammad, Fadil (CENDERAWASIH CONSTITUTIONAL REVIEW, 2025)
The simultaneous Regional Head Elections play a crucial role in creating participatory public policies. Active community participation in policy-making, supported by the values of deliberative democracy, ensures that decisions reflect the needs of the people. This research aims to understand and provide arguments for community involvement in the Regional Head Elections and its implications for the formation of public policy. This study employs a normative research method with a literature review approach and a legislative approach. The research findings indicate that the simultaneous Regional Head Elections have a crucial role in realizing participatory public policies. This political agenda not only focuses on the nomination and inauguration processes but also serves as a momentum to align national development with regional needs. Through the regional head elections, principles such as local accountability, political equality, and responsiveness can be realized, all of which contribute to strengthening democracy at the local level. Community participation in public policy formulation is an important foundation for the establishment of a democratic government. By actively involving the community, the decision-making process becomes more transparent and aligned with the aspirations and needs of the people. Various methods, such as discussion forums, public consultations, and digital platforms, enable the community to express opinions and provide input.